Moving Cages Further Offshore: Effects on Southern Bluefin Tuna, T. maccoyii, Parasites, Health and Performance - Kirchhoff, Nicole T.; Rough, Kirsty M.; Nowak, Barbara F. (PLOS ONE, 2011)
The effects of offshore aquaculture on SBT health (particularly parasitic infections and haematology) and performance were the main aim of this study. Two cohorts of ranched Southern Bluefin tuna (SBT) (Thunnus maccoyii) were monitored throughout the commercial season, one maintained in the traditional near shore tuna farming zone and one maintained further offshore. SBT maintained offshore had reduced mortality, increased condition index at week 6 post transfer, reduced blood fluke and sealice loads, and haematological variables such as haemoglobin or lysozyme equal to or exceeding near shore maintained fish. The offshore cohort had no Cardicola forsteri and a 5% prevalence of Caligus spp., compared to a prevalence of 85% for Cardicola forsteri and 55% prevalence for Caligus spp. near shore at 6 weeks post transfer. This study is the first of its kind to examine the effects of commercial offshore sites on farmed fish parasites, health and performance.